Kidnapping in the Pacific; Or, The Adventures of Boas Ringdon : A long four-part Yarn - Kingston, William Henry Giles, 1814-1880; Evans, Edmund, 1826-1905 (Salt Lake City, UT : Project Gutenberg, 2012)
"Kidnapping in the Pacific; Or, The Adventures of Boas Ringdon" by W.H.G. Kingston is a novel written in the mid-19th century. The book follows the escapades of its protagonist, Boas Ringdon, a young sailor who experiences life at sea, including encounters with slavers, hostile natives, and the piratical affairs of traders. The narrative explores themes of adventure, moral ambiguity, and colonial attitudes during a time when the Pacific islands were often exploited for labor and resources. The opening of the story introduces Boas and his fellow midshipmen who, after a shipwreck incident, seek refuge with an old white man living on a Pacific island. As they wait for their boat to be repaired, they learn about the man$1 (Bs past as a sailor involved in the slave trade, which serves as a grim backdrop to Boas's subsequent adventures. Boas reflects on his experiences, beginning from slave trading to attempts to capture native laborers for various schemes. The narrative quickly sets a tone of conflict and survival, with Boas constantly navigating a morally complex environment while establishing connections with characters both friend and foe. (This is an automatically generated summary.)s
Release date is 2012-09-06
Produced by Nick Hodson of London, England
Keywords: Kidnapping -- Juvenile fiction; Islands of the Pacific -- Juvenile fiction